No Association Between Statin Use and the Prognosis of Endometrial Cancer in Women With Type 2 Diabetes - Urpilainen, Elina; Ahtikoski, Anne; Arima, Reetta; Puistola, Ulla; Karihtala, Peeter (Frontiers in Pharmacology, 2021)
Preclinical studies have suggested statins have antiproliferative and anti-metastatic effects on endometrial cancer cells. Similarly, most previous epidemiological studies have reported a better prognosis of endometrial cancer in patients who used statins. In this study, we explored the role of statins in the prognosis of endometrial cancer in women with type 2 diabetes in a hospital-based cohort. This retrospective cohort consisted of 119 women with type 2 diabetes who were diagnosed and treated for endometrial cancer at Oulu University Hospital, Finland, between 2007 and 2014. The patients were classified as statin users (n = 58) and nonusers (n = 61) based on the type of medication they were using at the time of endometrial cancer diagnosis. Statin use showed no association with progression-free survival or overall survival in the whole cohort nor the subgroups with type I or type II histology, in lower or higher body mass index groups, or at an early or advanced stage. The results remained similar in the multivariate analysis after adjusting for the patient’s age, cancer stage, and histology. Furthermore, statin use seemed not to have any association with most of the prognostic factors at the time of endometrial cancer diagnosis.